Study on Development of Sustainable Livelihood Framework Approach at Indian Part of Sundarbans by Geospatial and Geo-statistical Analysis - Chatterjee, Sweta; Bhandari, Gupinath (Journal of Environmental Science and Economics, 2023)
Reclamation for settlement was started in 1770 at Sundarbans and the present population in the Indian part, is around 5.0 million, and gradually increasing, but continuous mangrove degradation made Sundarbans vulnerable. The Livelihood Structures for Sundarbans’ residents and amenities are largely dependent upon the Sundarbans’ resources, but these livelihood opportunities became vulnerable and face threats from several natural processes and anthropogenic activities. The present study attempted to understand the several dimensions of livelihood strategies for the inhabitants of several occupational groups at Sundarbans; associated opportunities, as well as constraints through the Sustainable Livelihood Framework (SLF) approach (after DFID, 2000) that envisages and comprises the livelihood assets, activities, important vulnerable issues that affect livelihood structures with the complex interactions amongst them. The objective of the present study is to establish a sustainable livelihood through the analysis of five important capitals of the SLF approach for the people of Indian Sundarbans considering the possible vulnerabilities. The same study has been carried out based on the extensive literature review, household livelihood surveys; informant interviews, and Shared Learning Dialogue (SLD) using the participatory approach by selected livelihood groups through several quantitative and qualitative indicators. The study concluded with the recommendation of Mangrove regeneration at Sundarbans.